Dynamic analysis of enhanced gear transmissions in the vehicle-track coupled dynamic system of a high-speed train. Issue 8 (3rd August 2022) - Wang, Zhiwei; Yin, Zhonghui; Allen, Paul; Wang, Ruichen; Xiong, Qing; Zhu, Yingmou
Abstract : Gear transmission is an essential element in the motor cars of high-speed trains, as it directly effects the reliability and safety of the vehicle. Based on the classical vehicle–track coupled dynamics theory, and gear and bearing dynamics theory, this investigation develops a novel vehicle–track coupled dynamics model with an enhanced gear transmission subsystem comprising gear pair and bearing. In the model, the enhanced gear transmission and vehicle–track system are coupled through suspension system, gear mesh interface, nonlinear bearing interaction and wheel–rail relationship, which enables detailed analysis of the gear transmission in the whole coupled system. Following the validation of the proposed model, the dynamic interactions between the gear pair and bearing are comprehensively investigated. Besides, the effects of the traction torque and track irregularities on the gear-bearing system are investigated. Results show that the gear meshing has significant influences on the bearings. The vehicle–track coupled environment has non-negligible effects on the dynamic interactions and vibrations of the gear transmission. Moreover, the proposed model is applicable to the further dynamic analysis of gears and bearings of the motor car under gear cracking, bearing failures, wheel defects and other destabilising conditions.